Exchange Rate Movements, Stock Prices and Volatility in the Caribbean and Latin America - Haughton, Andre Yone; Iglesias, Emma M. (International Journal of Economics and Financial Issues, 2017)
We analyse the interrelationship between stock prices and exchange rates in the only two Caribbean countries with stock market and floating exchange rates: Jamaica and Trinidad and Tobago. We also study the same four Latin American countries as in Diamandis and Drakos (2011). Using their model, our results show a very mild relationship between both variables in Jamaica, Trinidad and Tobago, Argentina and Brazil, but we cannot find any relationship in the other countries as in Diamantis and Drakos (2011). However, when we extend their model including a GARCH component to examine the impact of volatility, our results changed drastically: stock prices significantly impacted the exchange rate in the tranquil sub-period and the full period for Jamaica, over all three periods for Trinidad and Tobago and in the tranquil period for Argentina, Mexico and Chile. This shows the importance of incorporating volatility explicitly in the model. Our results have the policy implications that governments in the previous countries should try to prevent a currency crisis by stimulating economic growth and the expansion of the stock market to attract capital inflow as in Lin (2012). Keywords: exchange rates, stock prices, volatility. JEL Classifications: F31, G01